Distinct cultivars of Camellia oleifera and altitude affect proximate composition and lipidome profile of its seeds from two locations - Tiemin Jiang; Yuying Li; Bo Jie Chen; Yachun Lu; Xia Li; Hock Eng Khoo (Applied Food Research)
This study aimed to evaluate the proximate composition and lipidome profile of Camellia oleifera seed oil. The proximate composition of the seed samples was determined, including the total sugars, lipids, proteins, ash, and fibers. The results revealed a notable variation in their proximate composition. The seeds collected from plantations situated at a higher altitude exhibited an elevated lipid content. Significant discrepancies in the proximate composition were observed between the various Camellia cultivars. The identified lipid components were as follows: 39.69 % triglycerides, 11.43 % phosphatidylcholines, and the other lipid classes. Additionally, the findings indicated that there was a variation in the proportion of lipids among the distinct lipid classes in relation to the altitude of the plantation and the cultivars of the plant. Furthermore, a principal component analysis was performed on the four groups of CO seeds, which revealed that the predominant fatty acid identified in the seed oil was oleic acid.